GmGLU1 and GmRR4 contribute to iron deficiency tolerance in soybean - Kohlhase, Daniel R.; O’Rourke, Jamie A.; Graham, Michelle A. (Frontiers in Plant Science, 2024)
Iron deficiency chlorosis (IDC) is an abiotic stress that negatively impacts soybean yield. In a previous study, we demonstrated the historical IDC QTL on soybean chromosome Gm03 was composed of four distinct linkage blocks, each containing candidate genes for IDC tolerance. Here, we take advantage of virus induced gene silencing (VIGS) to validate the function of three high priority candidate genes, each corresponding to a different linkage block in the Gm03 IDC QTL. We built three single gene constructs to target GmGLU1 (GLUTAMATE SYNTHASE 1, Glyma.03G128300), GmRR4 (RESPONSE REGULATOR 4, Glyma.03G130000), and GmbHLH38 (beta Helix Loop Helix 38, Glyma.03G130400 and Glyma.03G130600). Given the polygenic nature of the iron stress tolerance trait, we also silenced the genes in combination. We built two constructs targeting GmRR4+GmGLU1 and GmbHLH38+GmGLU1. All constructs were tested on the iron efficient soybean genotype Clark grown in iron sufficient conditions. We found significant decreases in SPAD measurements using the GmGLU1 and both double constructs, with potential additive effects in the GmRR4+GmGLU1 construct. Whole genome expression analyses (RNA-seq) revealed a wide range of effected processes including known iron stress responses, defense and hormone signaling, photosynthesis and cell wall structure. These findings highlight the importance of GmGLU1 in soybean iron stress responses and provide evidence that IDC is truly a polygenic trait, with multiple genes within the QTL contributing to IDC tolerance. Finally, we use BLAST analyses to demonstrate the Gm03 IDC QTL is syntenic across a broad range of plant species.